(untitled) (Patan Prospective Journal, 2025)
The topic of this article is placed "Nepal - China Relationship during the Period of Chinese Cultural Revolution". The Chinese Cultural Revolution (1966–1976) is considered the biggest revolution after the Russian October Socialist Revolution in 1917. It was powerfully unfolded throughout China under the guidance of Mao Tsetung, the chairperson of the Chinese Communist Party (CPC). It has affected all sectors of society such as education, culture, politics, party, government, agriculture, industry, foreign affairs and so on. This was not a struggle against the political power of the opposite political party. Rather, according to Mao, the Cultural Revolution was carried out against the capitalist roaders who were sneaked into the Chinese Communist Party and its government and its bureaucracy. The objective of this article is to study the relationship between Nepal and China within the period of the Chinese Cultural Revolution. In this study, the qualitative method is used. Nepal has received huge aid from China. Araniko Highway was built. Indian Security Forces were removed from the northern border. Khampa Uprising was solved. So this period was a fruitful period for the Nepal - China relationship.